Model of Twin Automatic Stacking Crane Operation Strategy with Dynamic Handshake Area in an Automated Container Terminal - Putri, Maulin Masyito; Rusdiansyah, Ahmad; Nurminarsih, Siti (Institute of Research and Community Outreach - Petra Christian University, 2023)
This paper proposes a new idea for allocating a handshake area of an automated container yard. A block of automated container yards (CY) consists of two areas, which are the import (waterside) and export (landside) areas. The CY has two major activities (loading and unloading), where both are served by Twin Automatic Stacking Cranes (Twin-ASCs). A handshake area in the middle of the CY serves as a temporary slot for both ASCs. This situation causes an imbalance between the ASCs when the demands of each side differ significantly. Thus, we proposed using a dynamic location of the handshake area corresponding to the proportion demand of export and import containers. We developed a heuristics model and algorithms of ASC’s operations to compare the efficiency of the ASC operations between the fixed and the dynamic location. Based on our model and algorithm, we developed simulation software. Finally, we explored some numerical experiments to compare the performance of both policies in dealing with different export and import demand scenarios. Our result showed that the proposed approach outperformed the existing one in reducing unnecessary ASC movements.